Enhancing Native Language Pedagogy in Preschool Education: Integrating Cultural Contexts and Sustainable Development Goals (SDGs) - Khimmataliev, Dustnazar Omonovich; Sadikovich, Kiyamov Nishon; Mannapovna, Jabborova Onaxon; Qizi, Sayitova Umida Hikmatillo; Nematovna, Rakhmonova Zarifa; Bakhtiyarovna, Bilolova Zamira (International Journal of Language Education, 2025)
This study aims to enhance native language pedagogy in preschool by integrating interactive, digital, and culturally rooted methods in alignment with the Sustainable Development Goals (SDG 4 and SDG 11). A mixed-methods approach was employed, involving preschoolers and pre-service educators across various institutions. Quantitative data from vocabulary and comprehension tests, and qualitative insights from interviews and observations, showed that digital tools and cultural integration yielded greater language acquisition and engagement. Traditional methods underperformed in all indicators. Because language is deeply tied to identity and development, teaching practices that reflect culture and leverage innovation promote inclusivity, participation, and early literacy. These findings suggest that incorporating SDG-aligned strategies into educator training can foster educational equity and cultural sustainability in early learning environments.